Retinal nerve fiber layer thickness in diabetes mellitus versus normal population using optical coherence tomography - Erum Waris Khateeb; Qazi Afshana Sumaiya; Imtiyaz Ahmad Lone (Asian Journal of Medical Sciences, 2023)
Background: Diabetes mellitus is a micro vascular disorder that is on a rapid increase in number of diagnosed and undiagnosed cases, and it is estimated that approximately 191 million people may be suffering from this disorder by year 2030. It affects major vital organ and organ systems of the body, and is frequently accompanied with neuropathy, nephropathy, cardiovascular disorders and retinopathy. The quality of life of diabetic patients is significantly impacted by diabetic neuropathy. Aims and Objectives: To investigate the difference in peripapillary retinal nerve fibre layer (RNFL) thickness between normal population and Type-II diabetic patients without diabetic retinopathy using optical coherence tomography. Materials and Methods: Between May 2021 and May 2022, this case control research was conducted at Skims MCH Bemina SRINAGAR. Out of 400 eyes, 200 eyes belonged to healthy people and 200 eyes to Type II diabetics who did not have diabetic retinopathy. Age and gender were the same for both groups. Results: Mean age of study population was 47.05±5.47 years. Mean peripapillary RNFL thickness was 126.98±10.07 μm in Group-A (normal persons), and 120.77±5.41 μm in Group-B (Type-II diabetes). Between the two groups, there was a statistically significant difference in mean RNFL thickness as well as RNFL thicknesses in each quadrant (P=0.001). Conclusion: The diagnosis of any disease based on RNFL thinning must take into consideration the fact that diabetic patients have thin RNFL in comparison to normal persons.